(3SjQI Ydi Hf GdEeGe GdfGUQ UdGM GdOjf Hf GdegOis
(3ChdgG (B:s
(3Chdg eHJhQ hChd GdehLhO efg bhdg hCeG eMeO acGf ai PeGQ eY GdEeGe Ydjg GdSdGe hde jMVQ GdhGbYI hcGf GdeYSGd gPG eSJbQ Bd GdWGgQ heaRYge YfO GdfhGFH s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg (B: (3EPG cGf aI Lh GdSeG YQhbgG aCjf CYGdjgG hCjf GdPhGFH ef chY ai fejQ GdeLO hGQJhi hGYJOd ai OSJ GdecGQe hGSJhi s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJGQjNs